Association between the geriatric nutritional risk index and cognitive functions in older adults: a cross-sectional study from National Health and Nutrition Examination Survey - Tan, Zhichun; Nie, Yaxin; Yan, Ning (Frontiers in Nutrition, 2024)
Cognitive decline is a very serious problem in today's global aging environment. Failure to prevent and intervene in cognitive function may lead to irreversible deterioration of cognitive function, eventually progressing to cognitive impairment or even dementia, which is a heavy burden on individuals, families and even society as a whole. Cognitive decline can be prevented, especially through lifestyle interventions.Malnutrition is one of the most important risk factors for cognitive decline, and the GNRI, a simple index that effectively assesses the nutritional status of older adults, has been shown to be closely related to the prognosis and mortality of diabetes mellitus, stroke, depression, etc. The GNRI has been shown to be an effective indicator for assessing the nutritional status of older adults. However, there is still a lack of studies using a representative sample of the US. elderly population. We chose to conduct a cross-sectional study using data from the 2011-2014 U.S. National Health and Nutrition Examination Survey (NHANES) to examine the relationship between malnutrition and cognitive function.